STEAM Approach in Renewable Energy Education: Global Trends and Future Research Direction - Arief Puja Kesuma; Sunyono Sunyono; Dewi Lengkana; Een Yayah Haenilah; Rangga Firdaus; Muhammad Fuad; Ulul Azmi Muhammad (Jurnal Pendidikan Progresif, 2024)
STEAM Approach in Renewable Energy Education: Global Trends and Future Research Direction. Renewable energy education is an alternative to reducing fossil energy consumption at the school level in which students are hoped to save the energy in their living environment by playing a role in behavior in dealing with energy crises. Many studies regarding the use of STEAM approach to educate students on renewable energy have sharply grown. Objectives[LS1] ; This[LS2]  recent research aims to find the novelty of those previous studies regarding renewable energy education using STEAM approach for future researches. Method; a systematic review using bibliometric analysis was performed to carry out this research whereby 16 literatures indexed by Scopus and published in 2015 – 2021 were involved as the data. Several analyses, such as co-word, performance, citation, and co-authorship were used to analyze the data promoted by VOSviewer software. Fundings; the Results of this recent study showed that publication trend of renewable energy education studies involving the STEAM approach slightly increased in the period of 2015 – 2021 while citation trend sharply decreased. Several documents and lots of authors coming from some countries in each continent contributed most to the studies of STEAM approach in renewable energy education. Conclusion; some main themes such as country’s participant, environment, renewable energy, awareness, sustainability, education, learning approach, and competence also emerged to synthesize the prospectively new direction of future researches in renewable energy education using the STEAM approach. Keywords: bibliometric, renewable energy education, STEAM approach.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202492